PENGARUH PERSEPSI BIAYA PENDIDIKAN TERHADAP MINAT MELANJUTKAN PENDIDIKAN DI PRODI PENDIDIKAN EKONOMI FKIP UNRI PADA SISWA KELAS XII IPS SMA NEGERI DI KEC.TUALANG TAHUN 2018 - Gusdeliana Gusdeliana; Sri Kartikowati; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aim is to determine the effect of education costs on interest in continuing study at economic eduation study program of FKIP UNRI in student class XII IPS of State High School in Tualang District, 2018. This research used Purposive Sampling technique, which aims to determine the sample intentionally, in this research using the criteria of student which have an interest to continue study in Economic Education Study Program in FKIP UNRI of students class XII IPS at State High School with A accreditation in Tualang District Sample in this research is 73 respondent. Data analysis technique used is the classic assumption test used is the normality test. The hypothesis test used is simple linear regression with the help of SPSS version 19.0 and calculation using the formula manually. The result of reseacrh show that there is a positive and significant of education costs perception on interest in continuing study at economic education study program of FKIP UNRI in student class XII IPS State High School in Tualang District, 2018. This is evidenced by a simple linear regression analysis which obtained an Adjusted R Square value of 0.076, which can be interpreted the effect of Education Cost on the Interest in Continuing study in Economic Education Study Program is 7.6%. This means that when education costs are included in the affordable category according to students and parents, it will increase the interest of students to continue their study at Economic Education Study Program FKIP UNRI.Key Words: Interest in Continuing Study, Education Costs